The Optimization of NiO Doping, Thickness, and Extension in kV-Class NiO/Ga2O3 Vertical Rectifiers - Chao-Ching Chiang; Jian-Sian Li; Hsiao-Hsuan Wan; Fan Ren; Stephen J. Pearton (Crystals, 2023)
Ga2O3 heterojunction rectifiers have emerged as a novel candidate for various power conversion applications by using NiO as the solution on the p-type side. In this work, the optimized design of high-breakdown (1–7 kV), vertical geometry NiO/Ga2O3 rectifiers was examined using the Silvaco TCAD simulator to determine the electric field distribution for different NiO parameters. The doping concentration (1017–1019 cm−3), thickness (10–70 nm) of the guard ring, and its extension beyond the anode (0–30 µm) are all important in determining where the device breakdown occurs. Spatially, this can vary from the edge of the bilayer NiO extension to directly at the periphery of the top contact, consistent with experimental results. This transition phenomenon is proven to be correlated with the depletion effect by monitoring the depletion width when ramping up the bias and the doping concentration. The breakdown voltage was also calculated as a function of NiO top and bottom layer thicknesses and the doping concentration under different critical breakdown fields, where the latter is determined by the material quality of the drift layer.